LIM1 contributes to the malignant potential of endometrial cancer - Kato, Hiroaki; Saeki, Noritaka; Imai, Matome; Onji, Hiroshi; Yano, Akiko; Yoshida, Shuhei; Sakaue, Tomohisa; Fujioka, Toru; Sugiyama, Takashi; Imai, Yuuki (Frontiers in Oncology, 2023)
The incidence of endometrial cancer (EC) has been increasing worldwide. However, because there are limited chemotherapeutic options for the treatment of EC, the prognosis of advanced-stage EC is poor. To identify therapeutic targets, we analyzed gene expression profile datasets for EC cases registered in The Cancer Genome Atlas. Highly expressed genes in advanced-stage EC (110 cases) compared with early-stage EC (255 cases) were extracted and enriched with homeobox genes by Gene Ontology enrichment analysis. Among the identified genes, Kaplan-Meier plotter analysis of patients with EC showed that high LIM homeobox1 (LIM1) expression was associated with a significantly poorer prognosis. Additionally, LIM1 expression was significantly upregulated in high-grade EC cell lines (HEC50B cells). Knockdown of LIM1 in LIM1-knockdown (KD) HEC50B cells showed reduced cell proliferation and invasion. Ingenuity Pathway Analysis of RNA-seq data using LIM-KD cells revealed that the expression of CREB signaling-related genes was significantly suppressed and that phosphorylation of CREB was decreased in LIM1-KD cells. Furthermore, xenograft experiments revealed that tumor growth was significantly suppressed when CREB phosphorylation was decreased in LIM1-KD-derived tumors. Collectively, these results suggested that high LIM1 expression contributed to tumor growth via CREB signaling in EC.